Enhanced binding of tissue factor-microparticles to collagen-IV and fibronectin leads to increased tissue factor activity in vitro - Ettelaie, Camille; Collier, Mary E. W.; Mei, Mah Pui; Xiao, Yu Pei; Maraveyas, Anthony (Thrombosis and Haemostasis, 2013)
The role of tissue factor (TF)-containing microparticles in clot propagation has been established, but the ability of circulating microparticles to initiate coagulation has been disputed. However, TF-bearing microparticles, particularly endothelial-microparticles generated during disease, may interact with extracellular matrices which in turn can localise circulating TF to sites of injury. In order to examine this hypothesis in vitro, microparticles were isolated from human coronary artery endothelial cells transfected to overexpress TF, tumour-necrosis factor (TNF)α-treated cells or non-transfected cells lacking TF. The ability of microparticles to bind collagen-IV, fibronectin and fibrin was examined under static conditions and arterial shear rates (650 s-1), and also in the presence of inhibitory antibodies against β1-, β3-, α3-and αv-integrins or an anti-TF antibody. TF-microparticles showed increases of up to 43% and 24% in adherence to collagen-IV and fibronectin, respectively, compared to control microparticles under shear flow. Furthermore, TF-containing microparticles, but not the transfected parent cells had increased levels of β1-integrin compared to TF-deficient microparticles. Pre-incubation of microparticles with a β1-integrin-blocking antibody counteracted the additional adhesion of TFmicroparticles compared to control microparticles. Finally, adherence of TF microparticles to collagen-IV or fibronectin resulted in increased TF activity by concentrating TF onto the surface. In conclusion, the presence of TF within microparticles enhances the interactions of endothelial cell-derived microparticles with extracellular matrices in an integrin-dependent manner. Accumulation and localisation of these microparticles in turn results in the enhancement of TF activity. This may be an innate mechanism by which TF-bearing microparticles induce coagulation upon vascular injury.
Keywords: Tissue factor; endothelial-derived microparticles; extracellular matrices; integrins; procoagulant activity